2011
DOI: 10.1093/annonc/mdq707
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exemestane, anastrozole, and tamoxifen on lipid profiles in Japanese postmenopausal early breast cancer patients: final results of National Surgical Adjuvant Study BC 04, the TEAM Japan sub-study

Abstract: Changes of lipid profiles in Japanese postmenopausal women treated with tamoxifen were relatively favorable, while exemestane and anastrozole had no clinically significant effect on the serum lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 21 publications
2
40
0
2
Order By: Relevance
“…Although the targeted therapy trastuzumab has been associated with an increased risk of heart failure 16 , this agent was not available to treat BCS at the time this study was performed. Endocrine therapy with tamoxifen may reduce TC and LDL-C, while increasing TG levels 18 . A systematic review found that the use of aromatase inhibitors, compared with tamoxifen, was associated with increased odds of developing CVD and hypercholesterolemia 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the targeted therapy trastuzumab has been associated with an increased risk of heart failure 16 , this agent was not available to treat BCS at the time this study was performed. Endocrine therapy with tamoxifen may reduce TC and LDL-C, while increasing TG levels 18 . A systematic review found that the use of aromatase inhibitors, compared with tamoxifen, was associated with increased odds of developing CVD and hypercholesterolemia 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of traditional risk factors for CVD to chemotherapy [13][14][15] , radiotherapy 14 , targeted therapy 16 and endocrine therapy 17 may increase CVD risk in BCS. Use of endocrine therapy may be associated with favorable or unfavorable alterations in lipid profile 17,18 . CVD risk may be assessed by algorithms or mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received tamoxifen also had lower LDL levels at all time points (P .0001) and reduced lipoprotein parameters compared with patients who received anastrozole or exemestane. 34 Compared with anastrozole, exemestane was associated with significantly lower mean levels of cholesterol at 3 months and at 12 months (P .01 for both). 34 Mean triglyceride concentrations were significantly lower with exemestane compared with tamoxifen at all time points (P .0001) and compared with anastrozole at 3 months (P .01) and at 6 months (P .0001).…”
mentioning
confidence: 89%
“…34 Compared with anastrozole, exemestane was associated with significantly lower mean levels of cholesterol at 3 months and at 12 months (P .01 for both). 34 Mean triglyceride concentrations were significantly lower with exemestane compared with tamoxifen at all time points (P .0001) and compared with anastrozole at 3 months (P .01) and at 6 months (P .0001). 34 In the IES (N ¼ 4658), which assessed the impact of a switch to exemestane after 2 to 3 years of adjuvant tamoxifen, after 55.7 months of follow-up, hypercholesterolemia trended higher in the exemestane arm versus the tamoxifen arm (204 of 2320 patients [8.8%] vs 178 of 2338 patients [7.6%]; P ¼ .14), but the difference did not reach statistical significance (Table 2).…”
mentioning
confidence: 89%
“…How adjuvant regimens containing ais compare with the strategy of tamoxifen for 10 years is also unknown. 68 reported that tamoxifen had a favourable effect on lipid profiles and might be preferred over exemestane and anastrozole (both of which had no clinically significant effect on serum lipids) for patients at high risk of cardiovascular events such as hyperlipidemia. Two additional publications (abstracts only) 100,101 emerging from big 1-98 and atac provide an indirect comparison of anastrozole and letrozole, suggesting that letrozole could be more effective than anastrozole in reducing early distant recurrence and mortality rates at 5 years.…”
Section: Individual Studies and Comparison With Earlier Reviews And Mmentioning
confidence: 99%